Current perspectives of cognitive-behavioral therapy in the treatment of eating disorders: a systematic review (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
Studies show that young women aged between 12 and 28 years are most affected by eating disorders. An effective treatment for eating disorders is the cognitive behavioral therapy (CBT). This study aimed to analyzed the treatments that have been used in the area of cognitive-behavioral therapy for anorexia and bulimia in the past 5 years, through a systematic review conducted on June 24, 2014. The databases used were PubMed, PsychINFO and SCIELO in English, Spanish and Portuguese languages, and the search terms included cognitive therapy, behavior therapy, anorexia and bulimia. Were considered empirical studies and theory reviews with humans that were freely available. The analysis was done by two independent judges. A search in the databases provided 2066 articles. Abstracts of 26 studies that met the proposed criteria were analyzed. Were included 3 other studies identified from other sources. After analyzing in full, another 5 studies were eliminated and 24 completed all criteria. Of those, eleven with the term anorexia and 13 with bulimia, however, many did not address solely on these pathologies. It was concluded that CBT still proves to be effective in the treatment of eating disorders and studies suggest that current techniques cover a greater range of symptoms.
Keywords: Cognitive behavioral therapy; Anorexia nervosa; Bulimia Nervosa